Development of E-LKPD Assisted by FlippingBook Based on Environmath to Improve Metaphorical Thinking Skills - Ruhma, Salwa Zakiyah; Ratnaningsih, Nani; Rahayu, Diar Veni (Universitas Suryakancana, 2025)
This research aims to develop an E-LKPD integrated with FlippingBook technology based on the Environmath approach, as well as to investigate the enhancement of students’ metaphorical thinking skills before and after the implementation of the developed instructional materials. The study utilized a Research and Development (R&D) methodology guided by the ADDIE model, which comprises five sequential phases: analysis, design, development, implementation, and evaluation. Data were gathered through observations, expert validations of both material and media aspects, and assessments of students’ metaphorical thinking abilities. The participants involved in this study included two material experts, three media experts, and twenty seventh-grade students from MTs Miftahul Falah Panumbangan. The findings revealed that during the analysis stage, a needs analysis, student analysis, and material analysis were conducted. In the design stage, test instruments were prepared, media and format were selected, and the initial product design was developed. The development stage includes the product development process, while at the implementation stage, E-LKPD was tested on students. Furthermore, at the evaluation stage, it was found that there was a significant increase in metaphorical thinking skills after students used E-LKPD assisted by FlippingBook based on environmath with the quality of the increase being in the high category.